PERANCANGAN TEKSTIL DENGAN TEKNIK MARBLING DAN BATIK TULIS UNTUK BUSANA CASUAL - Amelia, Neneng Dela; Falah, Asep Miftahul; Atik, Saftiyaningsih Ken; Kudiya, Komarudin (ATRAT: Jurnal Seni Rupa, 2024)
This research presents an innovation in textile design for casual wear by combining marbling and batik techniques. The state of the art of the problem involves the need for unique and different casual wear, along with the increasing public interest in environmentally friendly and sustainable products. This research aims to produce interesting and unique textile designs and introduce traditional techniques such as batik tulis into casual wear. The method used is IDEO Method Cards, with the stages of Learn to learn marbling and batik tulis techniques, Look to see design inspiration, Ask to ask experts, and Try to try the techniques. The result is a casual fashion collection that is unique, artistic, and environmentally friendly. The recommendation of this research is to encourage further development in the use of traditional techniques in the modern fashion industry.